ASSESSMENT OF KNOWLEDGE AMONG NURSES REGARDING THE PREVALENCE OF MALNUTRITION IN CHILDREN UNDER THE AGE OF 5 YEARS - ANWAR, N; ASGHAR, S; ZARNIGAR, .; TESNEEM, SS; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Malnutrition remains a critical public health issue in Pakistan, significantly affecting children under five years of age. Nurses play a pivotal role in identifying, managing, and preventing malnutrition. However, their knowledge and practices regarding malnutrition prevalence often remain insufficient. Objective: This study aims to evaluate the knowledge, attitudes, and practices of nurses at a tertiary care hospital in Pakistan regarding malnutrition among children under five years of age. Methods: A descriptive cross-sectional study was conducted at Children’s Hospital Lahore over three months. A sample of 90 degree-holding staff nurses was selected using purposive sampling. Data were collected using a structured questionnaire covering demographics, knowledge about malnutrition forms, clinical features, risk factors, diagnostic methods, attitudes, and practices. Statistical analysis was performed using SPSS version 22.0 to calculate frequencies, percentages, and associations. Results: The study revealed significant knowledge gaps among nurses regarding malnutrition. Only 35.6% correctly identified Vitamin A deficiency as the most common form of malnutrition, and 47.8% incorrectly identified overweight as a clinical feature. Most nurses (46.7%) considered lack of education a key risk factor, while 41.1% cited poverty. Confidence in identifying malnutrition was low, with only 22.2% feeling very confident. Despite this, 75.6% reported screening children for malnutrition, and 82.2% used growth charts. However, only 1.1% of nurses expressed a strong willingness to provide nutritional education. Conclusion: The findings highlight critical gaps in the knowledge and attitudes of nurses, which could impact the quality of malnutrition care. While practices such as screening and documentation were common, limited confidence and willingness to provide education suggest a need for targeted training programs. Strengthening nurses’ capacity to manage malnutrition is essential to improving pediatric health outcomes in Pakistan.